Optimalisasi Peran Guru Dalam Proses Transformasi Nilai - Sari, Fatma (Al-Fikr: Jurnal Pendidikan Islam, 2019)
Study the role of the teacher as if it has never been finished to be studied because the role of the teacher has a big role in changes in students, both changes in self-quantity and self-quality. Changes in these two things need to be supported by several aspects, one of which is the optimal aspect of the teacher's role in playing each of his roles. What often happens in the learning process today is that not a few teachers play a role as instructors, transferring knowledge to students. Actually the needs of students are not only knowledge but also value, so that when teachers can optimize all their roles, what happens is that students not only increase their quantity in terms of science but also increase their quality in terms of mindset, speech, and behavior. Optimizing the role carried out by the teacher should be done comprehensively, starting from as a teacher, mentor, facilitator, and even motivator. To be a mentor, the teacher must have an understanding of the student being guided, understand the character and psychological structure. By understanding the concepts of guidance and counseling, the teacher is expected to be able to function as a guide. As a facilitator, the teacher can understand what the talents of his interests are, the teacher can build positive communication with parents of students and those who can help develop the talents of the students' interests and potential. As a motivator, teachers must understand the concepts and theories of motivation that are expected to help teachers to develop their skills in motivating their students to demonstrate superior learning or performance.